2006
DOI: 10.1038/ni1346
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic flagellin requires Ipaf for activation of caspase-1 and interleukin 1β in salmonella-infected macrophages

Abstract: Gram-negative bacteria that replicate in the cytosol of mammalian macrophages can activate a signaling pathway leading to caspase-1 cleavage and secretion of interleukin 1beta, a powerful host response factor. Ipaf, a cytosolic pattern-recognition receptor in the family of nucleotide-binding oligomerization domain-leucine-rich repeat proteins, is critical in such a response to salmonella infection, but the mechanism of how Ipaf is activated by the bacterium remains poorly understood. Here we demonstrate that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
1,016
3
28

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,069 publications
(1,086 citation statements)
references
References 45 publications
39
1,016
3
28
Order By: Relevance
“…They could show that S. typhimurium with a deficient flagellin does not stimulate caspase-1 or IL-1b secretion, and that intracellular flagellin activates an IPAF inflammasome, 100,101 a mechanism that does not require the other flagellin sensor TLR5. 100,101 Similarly, other studies showed that NAIP5, a mouse parologue of NAIP, possibly in combination with IPAF, recognizes intracellular flagellin from Legionella pneumophila, in order to induce caspase-1 activation. 61,102,103 Moreover, early genetic studies in mice clearly identified NAIP5 as a L. pneumophila susceptibility locus, further delineating the importance of inflammatory caspases in the control of bacterial pathogens.…”
Section: Intracellular Flagellin: Detection By the Nlr Proteins Naip mentioning
confidence: 90%
“…They could show that S. typhimurium with a deficient flagellin does not stimulate caspase-1 or IL-1b secretion, and that intracellular flagellin activates an IPAF inflammasome, 100,101 a mechanism that does not require the other flagellin sensor TLR5. 100,101 Similarly, other studies showed that NAIP5, a mouse parologue of NAIP, possibly in combination with IPAF, recognizes intracellular flagellin from Legionella pneumophila, in order to induce caspase-1 activation. 61,102,103 Moreover, early genetic studies in mice clearly identified NAIP5 as a L. pneumophila susceptibility locus, further delineating the importance of inflammatory caspases in the control of bacterial pathogens.…”
Section: Intracellular Flagellin: Detection By the Nlr Proteins Naip mentioning
confidence: 90%
“…Furthermore, flagellin appears to bind directly to TLR5 at residues 386-407, as TLR5 mutants lacking this domain are unable to interact with flagellin in biochemical assays (Mizel et al, 2003). Recent articles have demonstrated TLR5-independent recognition of cytosolic Salmonella typhimurium flagellin via Ipaf, a member of the NOD-LRR family (Franchi et al, 2006;Miao et al, 2006). Ipaf-mediated recognition of cytosolic flagellin induces caspase-1 activation and subsequent IL-1b secretion by macrophages.…”
Section: Bacterial Recognitionmentioning
confidence: 99%
“…Thus, activation of NLRC4 requires a two-hit process to induce IL-1β secretion: the first hit is the induction of pro-IL-1β and pro-IL-18 synthesis through activation of Toll-like receptor (TLR), and the second hit is the initiation of inflammasome assembly, which initiates caspase-1 self-cleavage and formation of the active heterotetrameric caspase-1. This cysteine-aspartic acid protease activates several proteins, including pro-IL-1β and pro-IL-18, and induces the secretion of both cytokines [24]. …”
Section: Introductionmentioning
confidence: 99%